Samurai and Silk : - Reischauer, Haru Matsukata (Belknap Press, 1986)
Reischauer, wife of a noted Japanese historian and former U.S. Ambassador to Japan, tells the story of her two grandfathers: the famous Meiji statesman Matsukata Masayoshi, whose stringent financial policies are credited with steering Japan safely through its first economic crisis, and Arai Rioichiro, who helped develop Japan's silk exports to the United States in the late 19th and early 20th centuries. Their lives, inextricably interwoven with modern Japanese history, are vividly presented, along with fascinating glimpses of the family life of Japan's upper class in this period. The book should be popular with general readers as well as specialists. Evelyn S. Rawski, History Dept., Univ. of Pittsburgh